The effect of the top soil layer on moisture and evaporation dynamics - Li, Z. (2021)
Results show that the top soil layer can significantly affect the evolution of soil moisture profiles and evaporation dynamics, the extent of which depends on the layering sequence, thickness, and properties of each layer. The soil systems consisting of a thick coarse (C) layer overlying a fine (F) layer, or a very thin F layer overlying a C layer exhibit near‐surface moisture, temperature and fluxes nearly identical to that of a homogeneous C system; in these cases, a homogeneous C soil could be used to represent the above two layered systems. However, some soil profiles cannot be described by a single set of soil properties, nevertheless, they show distinct characteristics that can serve as indicators for soil layering conditions, e.g., “first slowly then rapidly” decreasing dynamics of near‐surface soil moisture. As some characteristics are not unique to layered soil, the combined information including the near‐surface soil moisture defined at different depths and evaporation behavior of an entire drying cycle can be used to better characterize the layering conditions.